The effects of good governance and fraud prevention on performance of the zakat institutions in Indonesia: a Sharīʿah forensic accounting perspective - Wahyuni-TD, Ika Sari; Hasnah, Haron; Fernando, Yudi (Emerald Publsiher, 2021)
This study aims to investigate the direct and indirect effects of good governance and fraud prevention on the performance of Zakat institutions. This study aims to investigate the direct and indirect effects of good governance and fraud prevention on the performance of Zakat institutions. A theoretical model was developed based on stakeholder theory, and data were collected from Indonesian Zakat institutions through convenience sampling design. In total, 142 data sets were analysed using partial least squares-structural equation modelling statistical software. The results showed that good governance and fraud prevention significantly impact the performance of Zakat institutions. Yet, there was no significant influence of the fairness principle of good governance on Zakat performance in either direct or indirect relationships with fraud prevention. The results indicated that Zakat institutions as trusted agencies should pay more attention to fairness implementations to avoid fraud. Furthermore, fairness is an early signal that accountants can use to detect either fraudulent or mismanaged Zakat distribution. This paper provides the empirical justification for a theoretical model of Zakat performance that was conceptualized using good governance principles and Sharīʿah forensic accounting principles.